Influence of tool pin profiles on the filler added friction stir spot welded dissimilar aluminium alloy joints - M Balamurugan; Gopi S; Dhanesh G Mohan (Materials Research Express, 2021)
Dissimilar metals are pretty challenging to attain enhanced mechanical properties in the conventional friction stir spot welding (FSSW) process. In this research, a new filler added friction stir spot welding (FAFSSW) process is adopted for welding dissimilar aluminium alloys of AA5052 with AA6061 by using five different tapered tool pins to enhance the mechanical and metallurgical properties of the joints. Magnesium (Mg) powder with 4.5 mg in volume fraction is considered filler material to fabricate the joints. Mechanical properties of the spot weldments like tensile shear strength test, microhardness test, and metallurgical characterizations like microstructure analysis were carried out for FAFSSW joints. The results show that a tool pin profile with 5 mm upper diameter, 2 mm lower diameter and a pin length of 1.2 mm produce a sound joint with 202.85 MPa tensile shear strength and 119.9 HV microhardness. The FAFSSW joint shows 34% higher strength than the normal FSSW joints. The microstructure analysis indicates that the Mg filler mixes well in the weld zone, and a fine grain structure is gained without any defects.